The beekeeper's lament : how one man and half a billion honey bees help feed America - Nordhaus, Hannah (New York : Harper Perennial, 2011)
Recounts the experiences of John Miller, one of the foremost migratory beekeepers, who, despite mysterious epidemics that threaten American honey populations--and the nation's agribusiness--forges on and moves ahead in a new natural world.
Fast cars and big trucks -- Beekeeper's roulette -- The tiny leviathan -- Faustian bargains -- Trespasses -- Charismatic mini-fauna -- Survivor stock -- The human swarm -- Bittersweet bounty -- Next year, right?
Keywords: Miller, John; Bee culture -- United States; Honeybee -- United States; Migratory beekeepers -- United States